Interaction of Leadership Style and Work Environment: Implications for Employee Satisfaction - Surtinah , Wiwin; Istiatik, Dasih Irma; Winarto, Pawit; Maemunah, Sari (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
The objective of this study is to determine how the work environment and the style of leadership affect job satisfaction.   Sample penelitian terdiri dari tiga puluh tiga responden.   A survey was used as part of the data collecting process, along with samples and SPSS version 21 for analysis and testing.  According to the study's findings, workplace environment (H2) and leadership style (H1) both have a significant impact on employee job satisfaction. In addition, work environment (H2) and leadership style (H1) have a simultaneous effect on employee job satisfaction (Y).  Its management ramifications give managers and leaders strategic insights to establish a productive workplace environment and implement an appropriate leadership style. Managers need to understand that a supportive, communicative, and collaboration-oriented leadership style can increase employee engagement and satisfaction. In addition, ensuring a comfortable, safe, and productivity-supporting work environment is also an important factor that contributes to job satisfaction. Managers must continue to monitor and evaluate working conditions and provide training for leaders to improve their ability to understand employee needs.